Comparative analysis of education environment perception of 1st and 2nd year MBBS students of medical college using Dundee ready education environment measure - Amita Rajesh Ranade; Anita Jibhau Jadhav; Smita Wagh (Asian Journal of Medical Sciences, 2023)
Background: The Dundee ready education environment measure (DREEM) inventory is a useful tool to identify the student’s perception of the educational environment at the medical colleges. Aims and Objectives: This study aimed to evaluate and compare the perception of educational environment of 1st and 2nd year undergraduate medical students of SBH Government Medical College Dhule, using DREEM inventory. Materials and Methods: Eighty-six students of 1st year and 92 students of 2nd year MBBS participated in this study. DREEM questionnaire was given to the students in a classroom after the scheduled routine teaching sessions by the teachers. Students were instructed to indicate best response for each item given in DREEM questionnaire. Statistical analysis was performed using Microsoft Excel. Results: The mean score of 1st year student for each domain was comparatively higher than the score of 2nd year students. Items that have a mean score of 3.5 or over were considered to be real positive points. Items with a mean between 2 and 3 were aspects of the great concern that could be improve. Items with a mean of 2 or less indicate problem areas. The overall DREEM score was 141.96 (70.87%). However, there were no significant differences in the overall DREEM score of 1st and 2nd year students. The overall DREEM score of 1st and 2nd year students was 141.96 (70.87%). However, there were no significant differences in the overall DREEM score of 1st and 2nd year students. Conclusions: DREEM is a useful tool to assess the educational environment and to give a clear indication of the education environment perception of medical students. The DREEM questionnaire reflects the realistic situation in medical colleges and can be utilized in a variety of situations to obtain baseline information.